A Toxoplasma Prolyl Hydroxylase Mediates Oxygen Stress Responses by Regulating Translation Elongation - Florimond, Celia (mBio, 2019)
As the protozoan parasite Toxoplasma gondii disseminates through its host, it responds to environmental changes by altering its gene expression, metabolism, and other processes. Oxygen is one variable environmental factor, and properly adapting to changes in oxygen levels is critical to prevent the accumulation of reactive oxygen species and other cytotoxic factors. Thus, oxygen-sensing proteins are important, and among these, 2-oxoglutarate-dependent prolyl hydroxylases are highly conserved throughout evolution. Toxoplasma expresses two such enzymes, TgPHYa, which regulates the SCF-ubiquitin ligase complex, and TgPHYb. To characterize TgPHYb, we created a Toxoplasma strain that conditionally expresses TgPHYb and report that TgPHYb is required for optimal parasite growth under normal growth conditions. However, exposing TgPHYb-depleted parasites to extracellular stress leads to severe decreases in parasite invasion, which is likely due to decreased abundance of parasite adhesins. Adhesin protein abundance is reduced in TgPHYb-depleted parasites as a result of inactivation of the protein synthesis elongation factor eEF2 that is accompanied by decreased rates of translational elongation. In contrast to most other oxygen-sensing proteins that mediate cellular responses to low O(2), TgPHYb is specifically required for parasite growth and protein synthesis at high, but not low, O(2) tensions as well as resistance to reactive oxygen species. In vivo, reduced TgPHYb expression leads to lower parasite burdens in oxygen-rich tissues. Taken together, these data identify TgPHYb as a sensor of high O(2) levels, in contrast to TgPHYa, which supports the parasite at low O(2).